Taṭbīq Ṭarīqat Taḥlīl al-Akhṭāʾ fī Taʿlīm al-Insyāʾ al-ʿArabī al-Taḥrīrī - yoke suryadharma (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
The teaching of Arabic composition (al-insyāʾ) is a compulsory subject in many Islamic boarding schools (pesantren) in Indonesia. Alongside the development of Arabic language instruction, new teaching approaches have also emerged, one of which is Error Analysis. This approach constitutes a branch of Applied Linguistics and has its roots in earlier Arabic linguistic studies conducted by classical Arab scholars. Initially, Error Analysis was employed to investigate the linguistic differences between learners' native language and the target language from various linguistic perspectives. Today, however, the approach is primarily used to identify the actual difficulties encountered by learners during the language acquisition process. By examining the frequency and patterns of learners' errors, educators can determine the degree of difficulty of particular language problems and develop more effective instructional strategies. Consequently, Error Analysis has become widely applied in various areas of language teaching, including the instruction of written Arabic composition. This article explains the principles underlying the Error Analysis approach, discusses its objectives, and presents its practical application in teaching Arabic writing in a systematic and detailed manner.